Spontaneous Resolution of Congenital Intrahepatic Portosystemic Shunt - Tripathy, Taraprasad; Behera, Sandeep; Patel, Ranjan; Dutta, Tanmay; Kumar, Aditi; Satpathy, Amit Kumar (Acta medica Lituanica, 2024)
Congenital portosystemic shunts (CPSS) are a rare type of congenital abnormality. It results from abnormal embryonic development by the fourth week of fetal life. Congenital portosystemic shunts are believed to signify persistent communication between the portal and vitelline venous systems. Both extrahepatic and intrahepatic shunts are possible. They may develop on their own or in association with other congenital abnormalities. With regard to shunt type and size, symptoms vary widely. The anatomy of the shunt and associated abnormalities can be assessed by computed tomography and magnetic resonance angiography. The treatment plan is based on the type of shunt, its location and level of function, the patient’s age, and the severity of their symptoms.